2022
DOI: 10.3389/fbioe.2022.985696
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the di-c-glycosylation steps during biosynthesis of the antitumor antibiotic, kidamycin

Abstract: Kidamycins belong to the pluramycin family of antitumor antibiotics that contain di-C-glycosylated angucycline. Owing to its interesting biological activity, several synthetic derivatives of kidamycins are currently being developed. However, the synthesis of these complex structural compounds with unusual C-glycosylated residues is difficult. In the kidamycin-producing Streptomyces sp. W2061 strain, the genes encoding the biosynthetic enzymes responsible for the structural features of kidamycin were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…We previously reported the kid BGC from Streptomyces sp. W2061 (Heo et al, 2022), which is similar in content and organization to the known hedamycin BGC (Bililign et al, 2004). We also confirmed that Kid19, a ketosynthase of type II PKS, is responsible for the biosynthesis of the angucycline core (Heo et al, 2022).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…We previously reported the kid BGC from Streptomyces sp. W2061 (Heo et al, 2022), which is similar in content and organization to the known hedamycin BGC (Bililign et al, 2004). We also confirmed that Kid19, a ketosynthase of type II PKS, is responsible for the biosynthesis of the angucycline core (Heo et al, 2022).…”
Section: Resultssupporting
confidence: 73%
“…W2061 (Heo et al, 2022), which is similar in content and organization to the known hedamycin BGC (Bililign et al, 2004). We also confirmed that Kid19, a ketosynthase of type II PKS, is responsible for the biosynthesis of the angucycline core (Heo et al, 2022). In this study, we inactivated the type I PKS gene (kid13), which may be involved in the production of the aglycone side chain moiety.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations